Hard Working Character in Novel Entrok (Karakter Kerja Keras dalam Novel Entrok) - Ririn Setyorini (Jurusan Tadris Bahasa Indonesia, 2018)
In education, literature and learning are able to contribute considerably to the cultural, historical, social and literary patterns themselves. Literature is also able to provide a positive value for readers. The purpose of this study is to explain the value of the character of hard work on the character of Marni in the novel Entrok works Okky Madasari and its relevance to learning literature in college. This research is a qualitative descriptive research with data in the form of paragraph contained in novel Entrok Karya Okky Madasari. The sampling technique used is purposive sampling. Techniques of data collection using reading techniques, techniques of note, and interview techniques. Validate data with triangulation. Data were analyzed by content analysis. The results showed the value of character education of hard work that is relevant to the study of literature in universities, especially subjects of fiction assessment.Â Dalam pendidikan, sastra dan pembelajarannya mampu memberikan sumbangan yang cukup besar pada pola kebudayaan, sejarah, sosial, dan sastra itu sendiri. Sastra juga mampu memberikan nilai positif bagi pembacanya. Tujuan dari penelitian ini adalah menjelaskan nilai karakter kerja keras pada tokoh Marni dalam novel Entrok karya Okky Madasari serta relevansinya dengan pembelajaran sastra di perguruan tinggi. Penelitian ini merupakan penelitian deskriptif kualitatif dengan data berupa paragraf yang terdapat dalam novel Entrok Karya Okky Madasari. Teknik sampling yang digunakan adalah purposive sampling. Teknik pengumpulan data menggunakan teknik baca, teknik catat, dan teknik wawancara. Validasi data dengan triangulasi. Data dianalisis dengan analisis isi. Hasil penelitian menunjukkan adanya nilai pendidikan karakter kerja keras yang terelevansi dengan pembelajaran sastra di perguruan tinggi khususnya mata kuliah pengkajian fiksi.